1987
DOI: 10.1007/bf00269562
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation in plants regenerated from cultures of soybean

Abstract: Plants were regenerated from embryogenic and organogenic cultures derived from immature embryos of nine soybean (Glycine max L. Merr.) genotypes and extensive qualitative variation was noted in different regenerated families. Three lethal sectoral albinos were seen in the regenerated plants (R0). Variants observed in later selfed generations included twin seeds, multiple shoots, dwarfs, abnormal leaf morphology, abnormal leaflet number, wrinkled leaves, chlorophyll deficiency, partial sterility and complete st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 12 publications
1
23
0
2
Order By: Relevance
“…Although it is generally believed that plants regenerated via somatic embryogenesis would be less likely to display within-clone variation than plants regenerated via other in vitro routes [37], this has not been supported by data. No significant differences were found in frequencies of possible mutations for plantlets derived from embryogenic versus organogenic cultures [277], and embryogenic callus of maize was actually shown to produce a higher frequency of phenotypic variants than organogenic callus [278].…”
Section: B Factors Affecting Performance Of Somatic Embryo-derived Pmentioning
confidence: 96%
“…Although it is generally believed that plants regenerated via somatic embryogenesis would be less likely to display within-clone variation than plants regenerated via other in vitro routes [37], this has not been supported by data. No significant differences were found in frequencies of possible mutations for plantlets derived from embryogenic versus organogenic cultures [277], and embryogenic callus of maize was actually shown to produce a higher frequency of phenotypic variants than organogenic callus [278].…”
Section: B Factors Affecting Performance Of Somatic Embryo-derived Pmentioning
confidence: 96%
“…In most cases research on this was restricted to an evaluation of the morphology of a small number of plants and usually no obvious variation was found (Durham & Parrott, 1992;Gray & Mortensen, 1987;James et al, 1984;Klimaszewska, 1989;Lu & Vasil, 1981;. In Glycine max (Barwale & Widholm, 1987;Freytag et al, 1989;Shoemaker et al, 1991) this was studied in detail and variation for leaf shape, leaf variegation, growth habit, sterility, iso-enzyme patterns and lipid composition of seed could be observed. In most cases, it was found that these altered traits were heritable, showing that the variation was of genetic origin.…”
Section: Plant Propagationmentioning
confidence: 99%
“…The investigators demonstrated lowest heritability for albinism proposing that proportion of albino plants can be decreased by altering environmental and cultural conditions at various stages during the process of microspore culture in wheat. Few other experiments on this aspect highlighted that frequency of albino plants is under the control of one gene in soybean, barley, and maize (Barwale and Widholm 1987 ;Collins 1927 ;Neuffer et al 1997 ) while two or more loci are involved in peanut (Dwivedi et al 1984 ). In peanut, cytoplasm inheritance has also been shown to control albinism (Branch and Kvien 1992 ).…”
Section: Genetics and Genomics Of Albinism And Green Plant Regenerationmentioning
confidence: 94%